Analisis Semantik pada Kata “Afnān”: Kajian Mikro Linguistik Arab terhadap Surah al-Rahman Ayat 48 - Malia Fransisca (Fakultas Adab dan Humaniora UIN Sunan Ampel Surabaya, 2023)
Surah al-Rahman is one of the surahs in the Qur'an which has its own uniqueness, namely that there is 1 verse that is repeated up to 31 times, namely the verse that reads